006.07/658.562 Monitoring the effectiveness of the quality management system in manufacturing enterprises - xakimov, dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article analyzes scientific concepts, phrases and research results related to ensuring the effectiveness of the formation, implementation and management of a quality management system in manufacturing enterprises, and develops recommendations for assessing its effectiveness. A quality management system is a system that summarizes many years of experience of manufacturing enterprises and has absorbed all positive world practices that force enterprises to form certain quality practices, and has integrated all quality concepts into its philosophy. Monitoring the effectiveness of the quality management system in manufacturing enterprises is an important part of the enterprise's activities. This process is the basis for quality control, increasing production efficiency, and minimizing risks related to the quality of products or services.